Ongoing change in the structure of part-time employment - Karl Brenke (DIW Economic Bulletin, 2011)
The prominence of part-time employment has dramatically increased both in Germany and across Europe. Germany has experienced above- average growth and currently the prevalence of part-time employment there also exceeds the EU average. Evidently, this involves fundamental structural change as part-time employment has increased regardless of economic trends. Although part-time positions often still entail predominantly low-skilled work, the number of mediumskilled or highly qualified employees working shorter hours has also increased. Part-time employment has expanded into an increasing number of professions and occupations. The fact that the number of men in part-time work has increased particularly dramatically is further evidence of structural change. Nonetheless, reduced working hours remain unequivocally a woman's domain across the whole of Europe. Although the ratio of men to women in part-time employment in Germany has converged somewhat, the gender gap is still significantly larger than in most other European countries. Significant gender differences are also evident when we examine the reasons for part-time employment, both in Germany and in the EU as a whole: Women's motives are predominantly family- related, whereas men's motives are mainly linked to further vocational training and particularly the shortage of full-time positions. For many women, too, the lack of available jobs is a reason for working part-time as well. In spite of the fact that the employment situation in Germany has improved over the past few years, the number of employed people for whom a part-time job only represents a stopgap solution has leveled off at a substantial.
Keywords: J21; J22; 330; part-time work; Germany; EU